Effect of Alternanthera Species as Host Plant on Growth Performance of Seedlings of Indian Sandalwood (Santalum album L.) in Nursery - Durai, M. V.; Kartik, A. G.; Nawaj, Bande; Nagaraj, R. (Indian Forester, 2023)
No Abstract.